PLANNING VESSEL BODY SECTION PRODUCTION - A. G. Grivachevsky; V. D. Grivachevsky; M. Y. Kovalyov; A. I. Suhomlinov (Informatika)
A problem of planning production of a vessel body section is considered. The problem is reduced to the classic Johnson’s tree-machine flow-shop scheduling problem. A genetic algorithm and computer experiment to compare efficiency of this algorithm and the algorithm of full enumeration are described.